BRIDGING THE COGNITIVE GAP: TOWARD INTERCULTURAL PSYCHOLINGUISTIC FRAMEWORKS IN UZBEK-ENGLISH JOINT DEGREE PROGRAMS - Aminboeva Shakhriniso Ulugbekovna (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The expansion of joint degree programs between Uzbekistan and international partners is often viewed through a lens of administrative success. However, the lived experience of the student reveals a deeper challenge: the "psycholinguistic friction" encountered when moving between distinct media discourses. This paper argues that for international academic mobility to be truly effective, students must master the verbal-visual cues that shape meaning in both Uzbek and English contexts. By integrating psycholinguistic discourse analysis into joint curricula, we can move beyond mere language proficiency toward true intercultural competency.